APLICAÇÃO INDUSTRIAL DO GLICEROL OBTIDO A PARTIR DE TRANSESTERIFICAÇÃO DE ÓLEO DEGOMADO. - CESCA, Rafaela Silva; SILVA, Carmem Cícera Maria da; CARVALHO, Núbia Luiza Corrêa; MENDES, Luís Rodrigo Benitez (ANAIS DO ENIC, 2017)
-